Ответы и объяснения

Лучший Ответ!
  • Yuti
  • отличник
2013-05-11T17:19:55+04:00

(3a+2)/(a^2-2a+1)-6/(a^2-1)-(3a-2)/(a^2+2a+1)=(3a+2)/(a-1)^2-6/(a-1)*(a+1)-(3a-2)/(a+1)^2=((3a+2)*(a+1)^2-6(a-1)(a+1)-(3a-2)*(a-1)^2)/(a-1)^2*(a+1)^2  - преобразуем числитель.

(3a+2)*(a+1)^2-6(a-1)(a+1)-(3a-2)*(a-1)^2=(3a+2)*(a^2+2a+1)-6(a-1)(a+1)-(3a-2)*(a^2-2a+1)=3a^3+6a^2+3a+2a^2+4a+2-6a^2+6-3a^3+6a^2-3a+2a^2-4a+2=

6a^2+2a^2+2+6+2a^2+2=10a^2+10

(10a^2+10)/((a-1)^2*(a+1)^2 )=10(a^2+1)/(a^2-1)^2

Как-то так..